Maleic anhydride functionalization of OSTE based coatings via thiol-ene Click reaction for the covalent immobilization of xylanase - ÇAKMAKÇI, EMRAH; DEMİR, SERAP (ELSEVIER, 2017)
Combination of Off-Stoichiometry Thiol-Ene (OSTE) polymers with thiol-ene Click reaction is a versatile method for the development of advanced functional materials. In this study OSTE based photocurable coating materials with excess thiol groups on the surface were prepared and functionalized with maleic anhydride via thiol-ene Click reaction. Xylanase enzyme was then covalently immobilized onto these coatings. Maleic anhydride functionalization of the prepared OSTE coatings was proved by FTIR and contact angle measurements. The developed functional support was found to have high affinity for xylanase enzyme and the immobilization capacity was determined as 212 mg g(-1). Almost 100% of immobilization yield was achieved. Immobilization significantly improved the stability of the xylanase at pH values over 6.5 and temperatures exceeding 60 degrees C. Moreover the immobilized xylanase exhibited superior reusability and storage stability compared to free xylanase. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Thiol-ene Click reaction; OSTE; Covalent immobilization; Xylanase; Maleic anhydride; MAGNETIC NANOPARTICLES; ATTACHMENT; SUPPORT